Knowledge and attitudes toward euthanasia among final year pharmacy and law students: a cross-sectional study - Tidenek Mulugeta; Sintayehu Alemu (Taylor & Francis Group, 2023)
Abstract Background Euthanasia is the last resort for those living with untreatable and terminable diseases which cause pain and suffering. However, the concept of euthanasia resulted in many dilemmas and controversy around life extension and death. Objective The aim of this study was to evaluate the knowledge and attitudes of final year pharmacy and law students concerning euthanasia. Methods A descriptive cross-sectional study was carried out among all final year law and pharmacy undergraduate students. The data were collected using self-administered structured questionnaire and analyzed by SPSS version 22. Multivariate logistic regression was used to assess the influence of socio-demographic characteristics of participant's on acceptance of euthanasia. Result 72 (61.5%) of the students were declared that euthanasia is administration of lethal drugs to a patient at the explicit request of that patient. Majority 87 (74.4%) of the students knew that euthanasia is active shortening of the dying process. Most participants 95(81.2%) awared that there is no legalized euthanasia in Ethiopia. On the other hand, 47(40.2%) believed the patient has the right to choose to end his/her own life. Around 45% had the view that euthanasia should be legalized in some circumstances. Only 27.3% (n = 32) of the respondents endorsed legalization of euthanasia in Ethiopia. 35 (29.9%) said euthanasia should be performed. The acceptance of euthanasia was greater for pharmacy students compared to law students [adjusted odds ratio (AOR) = 3.490; 95% CI 1.346-9.049; p = 0.010] and lower for Muslim students compared to Orthodox students (AOR = 0.186; 95% CI 0.044-0.783; p = 0.022). Conclusion The final year law and pharmacy students were aware of euthanasia. However, majority of students did not reveal favorable attitude toward euthanasia and its acceptance was low. Participants' field of study and religion were significantly affect acceptance of euthanasia As the current study limited to pharmacy and law students, the authors suggest that future studies should involve various segments of societies to investigate more about euthanasia in Ethiopia.